Evaluation of Serum Lipid Profile During The Trimesters of Pregnancy (Medical Forum Monthly, 2024)
Background: During pregnancy, lipid metabolism is remarkably increased due to hormonal changes, which lead to various changes in serum lipid levels. Very high levels of lipids can have adverse effects on the maternal and foetal health.Objective: To analyze serum total cholesterol (TC), triglycerides (TGs), low density lipoprotein (LDL) and high density lipoprotein (HDL) in pregnant women during all trimesters.Study Design: Retrospective (hospital record based) studyPlace and Duration of Study: This study was carried out in Gynaecology and Obstetrics ward at Liaquat University Hospital, Jamshoro and Hyderabad from March 2011 to February 2012.Materials and Methods: 5ml blood sample was taken & analyzed for lipid profile using Hitachi 902 chemistry autoanalyzer. The data was analyzed by using SPSS 16. Results: The results showed that all these lipid parameters were raised during the all trimesters of pregnancy in comparison to the control subjects, except that the LDL level was almost equal to the control subjects during the 1st trimester. Additionally, comparison showed that Total Cholesterol, Triglycerides and LDL in the 2nd and 3rd trimesters were significantly higher than in the 1st trimester. Conclusion: Serum lipids are significantly increased during the all trimesters of pregnancy. As very high levels of lipids may increase the risk of development of various pregnancy complications for the mother and the developing foetus, lipid profile should be part of routine investigation during pregnancy